Chapter 7: Row Covers for Growth Enhancement - George J. Hochmuth; Robert C. Hochmuth (EDIS)
Row covers are flexible, transparent, or semitransparent materials used to enclose single or multiple rows of plants with the objective of moderating temperature and protecting from wind. This document is HS716, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date June 1995. Revised November 2006.